Chinese maritime relations with Malabar Coast, 1200–1500 AD: A quest for naval dominance. (3rd July 2019) - Chennattuserry, Joseph Chacko
ABSTRACT: China has had a long history of maritime expedition. Its Indian Ocean connectivity, long before European explorers arrived at the Malabar Coast, had made significant impact on the maritime trade in the Indian Ocean region. China's expedition to the Southern Asia was aimed to expand the benevolence of Chinese emperor and to establish its suzerainty in maritime trade rather than to establish the permanent position on land. The political dynamics at home caused the rise and fall of the maritime might of China. The famous explorer, Zheng He's expeditions represented China's ambition to expand its control over the Indian Ocean regions. The Malabar Coast with its geographical advantages had developed maritime activities enhancing its commercial fortunes. China had to accept the strength of Malabar kingdoms in terms of political power, trade and commercial advantages. Importantly, Malabar kingdoms did not accept the Chinese assertions of supremacy but engaged with the Chinese on equal terms. An attempt is made here to trace China's maritime strategy to expand their power beyond the immediate periphery and establish its supremacy in the Indian Ocean.